Defect in the uterine wall with prolapse of amniotic sac into it at 32 weeks' gestation in a primigravida woman without any previous uterine surgery. Issue 3 (18th November 2013) - Mishina, Miyuki; Hasegawa, Junichi; Ichizuka, Kiyotake; Oba, Tomohiro; Sekizawa, Akihiko; Okai, Takashi
Abstract We experienced a case of uterine wall defect with amniocele in a primigravida woman without any history of uterine surgery. On admission due to acute abdominal pain at 32 weeks' gestation, an ultrasound examination showed a 9 × 7‐cm sized echogenic cystic area in the Morrison pouch. Color Doppler revealed a flow from the uterus into the cystic area through a myometrial defect. During the operation, a 1‐cm defect in the uterine myometrium was found on the right fundus. An intact amniotic sac was prolapsed into the abdominal cavity through the myometrial defect. This was an extremely rare case of unexplained uterine wall defect.